A Normative Study of Objective Measures of Disparity Vergence and Saccades in Children 9 to 17 Years Old. Issue 6 (June 2020) - Namaeh, Mashael; Scheiman, Mitchell M.; Yaramothu, Chang; Alvarez, Tara L.
Abstract : SIGNIFICANCE: This study establishes normative data for objective outcome measures of vergence and saccade eye movements for the pediatric population. These data should facilitate future clinical trial design. PURPOSE: This study was designed to establish normative data for objective measures of disparity vergence and saccades in children between the ages 9 and 17 years using an objective binocular eye movement tracking system. METHODS: Participants (aged 9 to 17 years) had a vision examination including refraction, accommodative, and binocular vision testing. Eligibility criteria included 20/25 visual acuity with best correction, normal accommodation, and binocular vision. The ISCAN RK-826PCI binocular tracking system (ISCAN, Woburn, MA) was used to objectively record horizontal, symmetrical disparity vergence, and saccadic eye movements. Parameters assessed included peak velocity, time to peak velocity, latency, and response amplitude for both disparity vergence and saccades. RESULTS: One hundred eighteen participants were recruited (54.94% female; mean age, 13.5 years), and 77.1% (91/118) of the participants completed the assessment with usable data. A sample of the normative data included peak velocity (°/s), which had a mean ± standard deviation of 25.4 ± 2.9, 22.0 ± 3.0, 225 ± 16.7, and 332.5 ± 20.5 for 4° convergence, 4° divergence, 5° saccades, and 10° saccades, respectively. The mean ± standard deviation for the latency (seconds) measures were 0.28 ± 0.1, 0.28 ± 0.16, 0.23 ± 0.05, and 0.23 ± 0.05 for 4° convergence, 4° divergence, 5° saccades, and 10° saccades, respectively. CONCLUSIONS: Normative data enable researchers to have benchmark results for comparison with patient populations with binocular dysfunction. These objective disparity vergence measures can serve as outcome measures in future clinical trials to assess the effectiveness of therapeutic interventions by determining whether post-treatment results are similar to normal data.